The Effect of Work Motivation and Organizational Commitment on Employee Performance with Organizational Citizenship Behavior (Ocb) as an Intervening Variable in PKU Muhammadiyah Purbalingga General Hospital Employees - Alfatoni, M Sidiq; Widhiandono, Hengky; Akhmad Darmawan3, Akhmad; Hidayah, Arini (Asian Journal of Management Analytics, 2025)
This study was conducted to examine the impact of work motivation and organizational commitment on employee performance with OCB as an intermediate variable, at PKU Muhammadiyah Purbalingga Hospital. Using a quantitative approach, the data in this study was obtained from the results of a questionnaire on 121 employees from a total population of 223 people who were selected by aksinally using the Slovin formula. The data was analyzed using SEM-based Partial Least Square (PLS) through Smart PLS 4.00 software. The results revealed: (1) work motivation significantly had a positive effect on OCB and employee performance; (2) organizational commitment significantly has a positive effect on OCB and performance; (3) OCB is able to effectively mediate between work motivation and organizational commitment and performance; and (4) OCB itself has been proven to improve employee performance.